The role of renewable, non-renewable electricity consumption and carbon emission in development in Indonesia: Evidence from Distributed Lag Tests - Saudi, Mohd Haizam Mohd; Sinaga, Obsatar; Roespinoedji, Djoko; Razimi, Mohd Shahril Ahmad (International Journal of Energy Economics and Policy, 2019)
The current examination aims to explore the critical relationship of energy, in the form of electricity with economic growth of Indonesia. Contrary to traditional approach of assessing the impact of energy consumption, the present study analyzes the association from production point of view by assessing the impact of electricity production on economic development. In doing so, the current study has adopted the refined methodology of Auto-Regressive Distributed Lags (ARDL) bound testing approach to examine the dynamic relationship among renewable electricity generation, non-renewable electricity generation and economic growth with amplified understanding of the critical association to support the course of economic planning and policy making. The results of ARDL bound testing approach confirm that renewable electricity generation, non-renewable electricity generation and carbon dioxide emission are solid determinants of economic development in Indonesia. Moreover, the results avow that renewable electricity and non-renewable electricity generation have a useful and beneficial outcome on economic development in Indonesia Keywords: Renewable electricity generation, nonrenewable electricity generation, carbon dioxide emission, Indonesia. JEL Classifications: Q42, Q43 DOI: https://doi.org/10.32479/ijeep.7730